An appraisal of RECQ1 expression in cancer progression - Sharma, Sudha (Frontiers in Genetics, 2014)
RECQ1 is the most abundant member of the human RecQ family of DNA helicases genetically linked with cancer predisposition syndromes and well known for their functions in genome stability maintenance through DNA repair. Despite being the first discovered RecQ homolog in humans, biological functions of RECQ1 have remained largely underappreciated and its relevance to cellular transformation is yet unclear. RECQ1 is overexpressed and amplified in many clinical cancer samples. In silico evaluation of RECQ1 mRNA expression across the NCI-60 cancer cell lines predicts an association of RECQ1 with cancer cell migration, invasion and metastasis. Consistent with this, latest work implicates RECQ1 in regulation of gene expression, especially of those associated with cancer progression. Functionally, silencing RECQ1 expression significantly reduces cell proliferation, migration, and invasion. Collectively, these results propose that discerning the role of RECQ1 in conferring proliferative and invasive phenotype to cancer cells could be useful in developing therapeutic strategies to block primary tumor progression and metastasis.